Study of replenishment process w.r.t. Supply Chain Management at Torrent Pharmaceuticals Limited - Chawla, Prakash M. (Gyan Management Journal, 2013)
In 2008, the domestic pharma market in India was expected to be US$10.76 billion and this is likely to increase at 9.5 per cent,Jrom 2011 to 2015. This makes it 3"' globally in terms of volume {8% of global total) and 14th in terms of value (less than 1 % of global total). The company has adopted anticipatory responsive business model in replenishment process. The Primary Channel process is to transfer finished products from mother warehouse (manufacn;ring to mother warehouse) to carrying &forwarding agent. Subsequendy, the Secondary Channel is catering by fulfilling customer order from carrying & forwarding agent to Stockiest (wholesaler) to retailers.
Keywords: Replenishment Process; Periodic Review; Continuous Review; Responsive model